2022
DOI: 10.5433/1679-0359.2022v43n4p1705
|View full text |Cite
|
Sign up to set email alerts
|

Origanum vulgare extract as a natural additive in fresh cheese

Abstract: Oregano (Origanum vulgare) is a spice that has in its extracts and essential oils biological activities of interest, such as antimicrobial and antioxidant. These qualities are in line with the increased interest in natural alternatives for preserving foods such as fresh cheese due to its short shelf life. The objective of this research was to evaluate the acceptance, antibacterial and antioxidant activity of the hydroalcoholic extract of O. vulgare incorporated in fresh cheese during cold storage. For this, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In general, it was found that the addition of OLE significantly (p < 0.0001) increased the TP in all cheese samples as well as in the remaining whey, regardless of the coagulation method (p > 0.05). The obtained results are consistent with previously published data [8,[42][43][44][45]. The increase in TP corresponds to the increase in the effective concentration of the added OLE, except in the sample EM 25, where the TP was the highest, probably due to the variations in the dewatering process.…”
Section: Textural Parameters Of Ole Supplemented Cheese Curdssupporting
confidence: 92%
“…In general, it was found that the addition of OLE significantly (p < 0.0001) increased the TP in all cheese samples as well as in the remaining whey, regardless of the coagulation method (p > 0.05). The obtained results are consistent with previously published data [8,[42][43][44][45]. The increase in TP corresponds to the increase in the effective concentration of the added OLE, except in the sample EM 25, where the TP was the highest, probably due to the variations in the dewatering process.…”
Section: Textural Parameters Of Ole Supplemented Cheese Curdssupporting
confidence: 92%
“…Another widely studied potential of EOOV is its role as a preservative in animal products, especially cheeses (KIM; MARSHALL; WEI, 1995;GULLUCE et al, 2012;GURDIAN et al, 2017;BEDOYA-SERNA et al, 2018;KHORSHIDIAN et al, 2018;SANTOS et al, 2022). However, there are limitations in the use of this essential oil in the food industry because essential oils (EO) can change the organoleptic characteristics of the product and the constituents of the food can interact with the oil, thus causing an increase in the concentration needed to achieve the effect desired (TAJKARIMI; IBRAHIM; CLIVER, 2010; HYLDGAARD; MYGIND; MEYER, 2012).…”
Section: Hospital Clinical Isolates Of Drug-resistant Staphylococcus ...mentioning
confidence: 99%